The Role Of Pharmacists In Medication Prevention Error In Hospital - Mukriani Mukriani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Medication errors are a major problem for patient safety in hospitals, and can occur at any stage of the drug use process, from prescribing to monitoring therapeutic effects. Pharmacists, as healthcare professionals with specialized competencies in the field of drugs, play a strategic role in preventing medication errors. Objective: This article examines the role of pharmacists in preventing medication errors in hospitals. Methods: This article was written using literature​ review method, reviewing national and international journals, pharmacy textbooks, and relevant patient safety guidelines. Results: The study shows that the active involvement of pharmacists in the prescribing, dispensing, providing drug information, and monitoring drug therapy can significantly reduce the incidence of medication errors. Conclusion: Pharmacists play a crucial role in improving patient safety by preventing medication errors in hospitals. Optimizing the role of pharmacists requires support from hospital policies and interprofessional collaboration.